Kualitas Pelayanan Sekolah Minggu Terhadap Pembentukan Karakter Anak - Roni Hotmarice Damanik; Lasria Pasaribu; Damayanti Nababan (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
Sunday School is a church institution founded for the purpose of worship child. We hope that through learning children will grow and grow in their faith exemplify children's character so that they become strong individuals in God. The most important thing is the role of the family Parents are very important in fostering and supporting the development of faith and character.child. However, it cannot be denied that the complete foundation of education includes: Overall it consists of four pillars, and in fact the first pillar is the family whose source is the parents.